2019
DOI: 10.1088/1361-6528/aafd53
|View full text |Cite
|
Sign up to set email alerts
|

Probing the mechanical properties of vertically-stacked ultrathin graphene/Al2O3 heterostructures

Abstract: The superior intrinsic mechanical properties of graphene have been widely studied and utilized to enhance the mechanical properties of various composite materials. However, it is still unclear how heterostructures incorporating graphene behave, and to what extent graphene influences their mechanical response. In this work, a series of graphene/Al2O3 composite films were fabricated via atomic layer deposition of Al2O3 on graphene, and their mechanical behavior was studied using an experimental-computational app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 36 publications
3
14
2
Order By: Relevance
“…For the nano-GO particles, two bands were observed where the first band (D) was seen at 1341 cm −1 and the second band (G) was observed at 1584 cm −1 (Figure 4A). Due to the energy shift caused by laser excitation, observing two peaks on Raman spectroscopy is a common observation for graphite based materials [45], as seen in our study. It is a common finding to observe the characteristic P-O band at 960 cm −1 for HA samples in Raman spectroscopy [46].…”
Section: Discussionsupporting
confidence: 64%
“…For the nano-GO particles, two bands were observed where the first band (D) was seen at 1341 cm −1 and the second band (G) was observed at 1584 cm −1 (Figure 4A). Due to the energy shift caused by laser excitation, observing two peaks on Raman spectroscopy is a common observation for graphite based materials [45], as seen in our study. It is a common finding to observe the characteristic P-O band at 960 cm −1 for HA samples in Raman spectroscopy [46].…”
Section: Discussionsupporting
confidence: 64%
“…The Micro-Raman representative spectra of rGO-5% adhesive demonstrated two vibrational bands; the D band was seen at 1341 cm −1 whereas the G band was perceived at 1584 cm −1 , and this particular finding was similar to a previous study [ 25 ]. For the materials having graphite, the observation of two bands is common as they are created due to the shift in energy caused by the laser excitation [ 34 ]. Concerning resin tags, rGO-5% demonstrated comparable resin tags ( Figure 4 A–C) to EA-rGO-0%.…”
Section: Discussionmentioning
confidence: 99%
“…The failure morphology in Figure c suggests that during the fracture propagation process, the strain energy in thicker films can be released by forming through-thickness cracks while, on the contrary, the thinner films release the energy by forming more in-plane cracks that cause film rupture and delamination. Failure of amorphous alumina films at the nanoscale has been reported to be brittle; however, several recent studies reported plastic deformation for alumina films of 50 and 35 nm thick. , Herein, deviations from linear behavior and minor force drops were evident in the failure F –δ curves of the 50C-, 100C-, and 150C-Al 2 O 3 @G films immediately before failure, which was highlighted in Figure S6. These deviations from linearity were likely due to the yield and initiation of plastic deformation at high forces just before the major fracture.…”
Section: Results and Discussionmentioning
confidence: 93%
“…The moduli of a-Al 2 O 3 @G films were in reasonable agreement with ROM above ∼3.3 nm with an estimated bulk value of 166 GPa. The gray band shows the range of E values of alumina films of 5–200 nm presented in Table S1. ,,, …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation